2018
DOI: 10.1093/gigascience/giy012
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome of the protandrous Chinese black porgy, Acanthopagrus schlegelii

Abstract: BackgroundAs one of the most popular and valuable commercial marine fishes in China and East Asian countries, the Chinese black porgy (Acanthopagrus schlegelii), also known as the blackhead seabream, has some attractive characteristics such as fast growth rate, good meat quality, resistance to diseases, and excellent adaptability to various environments. Furthermore, the black porgy is a good model for investigating sex changes in fish due to its protandrous hermaphroditism. Here, we obtained a high-quality ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 63 publications
1
55
1
Order By: Relevance
“…Sparidae genetic data have been recently greatly enriched by transcriptomic studies (Tsakogiannis et al, 2018; Manousaki et al, 2014) and two whole-genome sequencing datasets, those of gilthead seabream (Pauletto et al, 2018) and Chinese black porgy (Zhang et al, 2018). In the phylogenomic analysis of Pauletto et al using 2,032 genes from 14 species, the large yellow croaker ( Larimichthys crocea , family: Sciaenidae) and the European seabass ( Dicentrarchus labrax , family: Moronidae) were placed as sister groups to gilthead seabream with high confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Sparidae genetic data have been recently greatly enriched by transcriptomic studies (Tsakogiannis et al, 2018; Manousaki et al, 2014) and two whole-genome sequencing datasets, those of gilthead seabream (Pauletto et al, 2018) and Chinese black porgy (Zhang et al, 2018). In the phylogenomic analysis of Pauletto et al using 2,032 genes from 14 species, the large yellow croaker ( Larimichthys crocea , family: Sciaenidae) and the European seabass ( Dicentrarchus labrax , family: Moronidae) were placed as sister groups to gilthead seabream with high confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Raw reads were filtered first to remove low-quality reads and adaptor sequences by SOAPnuke 20 . Clean reads were mapped to the reference genome of B. terrestris (GenBank: GCF_000214255.1) using Bowtie2 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The osmosensory signalling networks, controlling above effector genes, are most obvious and effective in euryhaline species involving in osmoregulatory mechanism (Kültz 2012). Moreover, several genomic datasets of Sparidae fish have been published in recent years, such as those for A. schlegelii (Zhang et al, 2018), S. aurata (Pauletto et al, 2018), and red seabream (Pagrus major) (Shin et al, 2018). However, no genomic research has been conducted thus far to identify the candidate genes and pathways for survival over a large range of salinities, which severely hinders studies examining their osmoregulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in gilthead sea bream (Sparus aurata), fast evolution is observed only for highly ovary-biased genes due to female-specific patterns of selection that are related to the peculiar reproduction mode (Pauletto et al, 2018). By performing a comparative genomic analysis, Zhang et al (2018) found three types of genes that are potentially associated with sex reversal and are useful for studying the genetic basis of protandrous hermaphroditism in black seabream (Acanthopagrus schlegelii). Moreover, comparative transcriptomic analyse has been conducted to identify the male-and female-specific genes and pathways that are most likely involved in sex maintenance in Sparidae (Tsakogiannis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%